2014
DOI: 10.3402/gha.v7.24085
|View full text |Cite
|
Sign up to set email alerts
|

Supervising community health workers in low-income countries – a review of impact and implementation issues

Abstract: BackgroundCommunity health workers (CHWs) are an increasingly important component of health systems and programs. Despite the recognized role of supervision in ensuring CHWs are effective, supervision is often weak and under-supported. Little is known about what constitutes adequate supervision and how different supervision strategies influence performance, motivation, and retention.ObjectiveTo determine the impact of supervision strategies used in low- and middle-income countries and discuss implementation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
185
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(217 citation statements)
references
References 72 publications
10
185
0
5
Order By: Relevance
“…This finding accords with research, which suggests that supervision and feedback significantly improve CHW performance . Higher quality of supervision contributes to better CHW performance just as much as increased frequency of supervision . Therefore, improving the clinical skills of LHSs along with more frequent field visits where they could repeatedly demonstrate correct clinical practices was likely to have improved LHW skills .…”
Section: Discussionsupporting
confidence: 85%
“…This finding accords with research, which suggests that supervision and feedback significantly improve CHW performance . Higher quality of supervision contributes to better CHW performance just as much as increased frequency of supervision . Therefore, improving the clinical skills of LHSs along with more frequent field visits where they could repeatedly demonstrate correct clinical practices was likely to have improved LHW skills .…”
Section: Discussionsupporting
confidence: 85%
“…HEWs who were supervised biannually were less like to have a good practice on drug provision than those who were supervised monthly. This finding is consistent with studies conducted in Uganda and other low-income countries [50,51]. Besides, HEWs who had no national guidelines were less likely to have a good practice of drug provision than those who had national guidelines.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that support supervision is critical for improving the performance of CHWs (11). However, despite its importance, the implementation of support supervision has been identified as a weak link in many CHW programs (31, 32). Yet, it is not clear how this can be effectively implemented (33).…”
Section: Discussionmentioning
confidence: 99%